2012
DOI: 10.1111/j.1467-8624.2012.01764.x
|View full text |Cite
|
Sign up to set email alerts
|

12‐Month‐Olds’ Phonotactic Knowledge Guides Their Word–Object Mappings

Abstract: This study examined whether 12-month-olds will accept words that differ phonologically and phonetically from their native language as object labels in an associative learning task. Sixty infants were presented with sets of English word-object (N = 30), Japanese word-object (N = 15), or Czech word-object (N = 15) pairings until they habituated. Infants associated CVCV English, CCVC English, and CVCV Japanese words, but not CCVC Czech words, with novel objects. These results demonstrate that by 12 months of age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
93
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(100 citation statements)
references
References 29 publications
5
93
2
Order By: Relevance
“…Infants readily learned novel object labels that consisted of legal phoneme combinations in English, but failed to learn labels that contained illegal phoneme combinations. MacKenzie, Curtin, and Graham (2012) also found that 12-month-olds failed to learn phonotactically illegal object labels. Later in development, a similar pattern is apparent for labels that are phonotactically legal, but differ in probability.…”
Section: Learning About Phonotacticsmentioning
confidence: 90%
See 2 more Smart Citations
“…Infants readily learned novel object labels that consisted of legal phoneme combinations in English, but failed to learn labels that contained illegal phoneme combinations. MacKenzie, Curtin, and Graham (2012) also found that 12-month-olds failed to learn phonotactically illegal object labels. Later in development, a similar pattern is apparent for labels that are phonotactically legal, but differ in probability.…”
Section: Learning About Phonotacticsmentioning
confidence: 90%
“…Infants’ ability to discriminate sound sequences does not necessarily indicate that they treat them as functionally distinct (e.g., Stager & Werker, 1997). However infants do differentiate phonotactically legal versus illegal object labels (Graf Estes et al, 2011; MacKenzie et al, 2012) and may do the same for high versus low phonotactic probability labels. Finally, how do prosodic and phonotactic regularities interact in word learning?…”
Section: Integrating Prosody and Phonotactics In Word Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…By 12 months, English-learning infants are able to attach phonotactically legal words to novel objects, but not illegal words (MacKenzie et al, 2012;see Graf-Estes et al, 2010 for similar results at 18 months). By tracking highly probable combinations of speech sounds, infants can recognize these forms as good word candidates.…”
Section: ------------[Figure 4 Here] -----------General Discussionmentioning
confidence: 89%
“…Twelve-month-olds map novel words containing legal onsets onto objects (e.g., plot), but not those that contain illegal ones (e.g., ptak; MacKenzie, Curtin, & Graham, 2012).…”
mentioning
confidence: 99%